The Role of HSA21 Encoded Mirna in Down Syndrome Pathophysiology:Opportunities in miRNA-Targeted Pharmacotherapy and Diagnosis of the Down Syndrome - Shabnam Mahernia; Sajad Sarvari; Yousef Fatahi; Massoud Amanlou (Tabriz University of Medical Sciences, 2021)
Trisomy 21 is the most prevalent aneuploidy disorder among live-born children worldwide. Itresults from the presence of an extra copy of chromosome 21 which leads to a wide spectrum ofpathophysiological abnormalities and intellectual disabilities. Nevertheless human chromosome21 (HSA21) possess protein non-coding regions where HAS-21 derived-microRNA genes aretranscribed from. In turn, these HSA21-derived miRNAs curb protein translation of severalgenes which are essential to meet memory and cognitive abilities. From the genetics andmolecular biology standpoints, dissecting the mechanistic relationship between DS pathology/symptoms and five chromosome 21-encoded miRNAs including miR-99a, let-7c, miR-125b-2,miR-155 and miR-802 seems pivotal for unraveling novel therapeutic targets. Recently,several studies have successfully carried out small molecule inhibition of miRNAs function,maturation, and biogenesis. One might assume in the case of DS trisomy, the pharmacologicalinhibition of these five overexpressed miRNAs might open new avenues for amelioration of theDS symptoms and complications. In this review, we primarily elucidated the role of HSA21-encoded miRNAs in the DS pathology which in turn introduced and addressed importanttherapeutic targets. Moreover, we reviewed relevant pharmaceutical efforts that based theirgoals on inhibition of these pathological miRNAs at their different biogenesis steps. We havealso discussed the challenges that undermine and question the reliability of miRNAs as noneinvasivebiomarkers in prenatal diagnosis.